Impact of changing from a guaiac faecal occult blood test to a faecal immunochemical test in a national screening programme: Results from a pilot study within the national bowel cancer screening programme in England. (December 2021) - Benton, Sally C; Piggott, Carolyn; Blyuss, Oleg; Li, Shuping J; Mathews, Christopher; Carroll, Magdalen; Duffy, Stephen
Objective: Testing for occult blood in faeces is widely used in bowel cancer screening around the world. In many programmes, the faecal immunochemical test (FIT) is replacing the traditional guiaic faecal occult blood test (gFOBT). There have been a number of reports on the clinical impact of making this change; yet, no-one has considered the pre-analytical and analytical impact of moving from a gFOBT to a FIT bowel cancer screening programme. Methods: We interrogated data obtained in a FIT pilot carried out in England in 2014 to assess the timeliness of specimen collection device return time and analysis for gFOBT and FIT, the impact of time to analysis on faecal haemoglobin (f-Hb) concentration, and any differences observed between analyses carried out at two different testing laboratories. Results: FIT kits were returned on average 5.6 days sooner than gFOBT. The time to analysis for FIT leads to an overall rise in f-Hb concentration within the manufacturer's stated 14-day stability period. Conclusion: Both these factors are important considerations for laboratories when considering setting up a bowel cancer screening programme, especially if transitioning from gFOBT to FIT. Our data also support previous evidence of males having a higher f-Hb than females and demonstrate that after adjusting for sex, age and screening hub, neither index of multiple deprivation nor screening episode significantly affected f-Hb.